Dual-specificity phosphatase 6 (DUSP6): a review of its molecular characteristics and clinical relevance in cancer - Ahmad, Muhammad Khairi; Abdollah, Nur Ainina; Shafie, Nurul Husna; Mohd Yusoff, Narazah; Abdul Razak, Siti Razila (China Anti-Cancer Association, 2018)
Mitogen-activated protein kinases (MAPKs) are the main regulators of cellular proliferation, growth, and survival in physiologicalor pathological conditions. Aberrant MAPK signaling plays a pivotal role in carcinogenesis, which leads to development andprogression of human cancer. Dual-specificity phosphatase 6 (DUSP6), a member of the MAPK phosphatase family, interacts withspecifically targeted extracellular signal-regulated kinase 1/2 via negative feedback regulation in the MAPK pathway of mammaliancells. This phosphatase functions in a dual manner, pro-oncogenic or tumor-suppressive, depending on the type of cancer. Todate, the tumor-suppressive role of DUSP6 has been demonstrated in pancreatic cancer, non-small cell lung cancer, esophagealsquamous cell and nasopharyngeal carcinoma, and ovarian cancer. Its pro-oncogenic role has been observed in humanglioblastoma, thyroid carcinoma, breast cancer, and acute myeloid carcinoma. Both roles of DUSP6 have been documented inmalignant melanoma depending on the histological subtype of the cancer. Loss- or gain-of-function effects of DUSP6 in thesecancers highlights the significance of this phosphatase in carcinogenesis. Development of methods that use the DUSP6 gene as atherapeutic target for cancer treatment or as a prognostic factor for diagnosis and evaluation of cancer treatment outcome hasgreat potential. This review focuses on molecular characteristics of the DUSP6 gene and its role in cancers in the purview ofdevelopment, progression, and cancer treatment outcome.